Has Stock Markets' Reaction to Terrorist Attacks Changed throughout Time? Comparative Evidence from a Large and a Small Capitalisation Market - Christos Kollias; Efthalia Manou; Stephanos Papadamou; Apostolos Stagiannis (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
An expanding body of literature has addressed the question of the economic impact terrorist attacks have. A part of this literature has focused on the impact recent major terrorist hits had on financial markets. The question addressed by this paper is to what extent markets' reaction to major terrorist hits has changed over time. A large - the London stock exchange - and a small - the Athens stock exchange - capitalization market are used as the vehicles for the empirical investigation. Results from event study methodology as well as from conditional volatility models used here do no seem to point to any clear and unequivocal picture. Both markets appear to react selectively to terrorist events with no evidence of a noticeable change through time. Generally the effects appear to be transitory in both markets and seem to depend on the political and symbolic significance of the target hit. Market size and maturity also seem to influence the degree of the effects.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: G14; G21; C22; 330; terrorism; financial markets; volatility; event study